2012
DOI: 10.1016/j.molcel.2012.09.029
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Complex 2 Regulates Proper Turnover of Insulin Receptor Substrate-1 via the Ubiquitin Ligase Subunit Fbw8

Abstract: SUMMARY The mammalian target of rapamycin (mTOR) integrates signals from nutrients and insulin via two distinct complexes, mTORC1 and mTORC2. Disruption of mTORC2 impairs the insulin-induced activation of Akt, an mTORC2 substrate. Here we found that mTORC2 can also regulate insulin signaling at the level of insulin receptor substrate-1 (IRS-1). Despite phosphorylation at the mTORC1-mediated serine sites, which supposedly triggers IRS-1 downregulation, inactive IRS-1 accumulated in mTORC2-disrupted cells. Defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 46 publications
3
97
0
3
Order By: Relevance
“…Recently, it was reported that mTORC2 could trigger IRS1 degradation via Fbw8 stablization [24]. However, the same study also reported that depletion of SIN1 led to insufficient activation of InsR and reduced PIP3 production [24]. Our current finding highlights the first important interaction between mTORC2 and IGF-IR/InsR, and identifies IRS1/2 as important mediators of this interaction.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Recently, it was reported that mTORC2 could trigger IRS1 degradation via Fbw8 stablization [24]. However, the same study also reported that depletion of SIN1 led to insufficient activation of InsR and reduced PIP3 production [24]. Our current finding highlights the first important interaction between mTORC2 and IGF-IR/InsR, and identifies IRS1/2 as important mediators of this interaction.…”
Section: Discussionsupporting
confidence: 58%
“…Phosphorylation of IRS1/2 by mTOR and S6K1 then leads to their proteasomal degradation [38][39][40]. Recently, it was reported that mTORC2 could trigger IRS1 degradation via Fbw8 stablization [24]. However, the same study also reported that depletion of SIN1 led to insufficient activation of InsR and reduced PIP3 production [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies already linked the proteasome-mediated degradation of IRS1 to the inhibition of insulin action in response to hyperinsulinaemia [35,36] and inflammation [37]. In this context, multiple E3-ligases, including F-box only protein 40, CBLB, and F-box/WD repeat-containing protein 8, have been linked to IRS1 degradation in response to hyperinsulinaemia, inflammation and chronic exposure to insulin-like growth factor 1 [37][38][39][40][41]. Furthermore, increased expression of Fbxo32 and Murf1 associated with reduced activation of the PI3K/Akt pathway by insulin was described in skeletal muscle of db/db mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that CRL7-induced degradation of IRS1 is part of a negative feedback loop via mechanistic target of rapamycin complex 1 (mTORC1) to restrain IRS1 downstream signaling (17,19). A more recent study suggested an mTORC2-dependent feedback inhibition of IRS1 by direct phosphorylation of Fbw8, resulting in enhanced stability of this F-box protein that promotes IRS1 degradation (20). Collectively, these studies have implicated roles for CRL7 in regulating both mTORC1 and mTORC2 signaling.…”
mentioning
confidence: 99%